Digital Health and Professional Identity in Australian Health Libraries: Evidence from the 2018 Australian Health Information Workforce Census - Gilbert, Cecily; Gray, Kathleen; Butler-Henderson, Kerryn; Ritchie, Ann (Evidence Based Library and Information Practice, 2020)
Objective – This research aimed to examine the characteristics of the current health library professional workforce in Australia. The study also sought to explore the areas of health library competency domains and job functions that may reflect progress toward a specialized digital health information capability.Methods – Health librarians’ responses to the May 2018 Australian Health Information Workforce Census were analysed and compared with results obtained in earlier census counts. The health librarian characteristics were also compared with other health information occupations included in the Census.Results – There were 238 usable health librarian responses. These indicate that the health librarian workforce continues to be a comparatively mature population, with substantial experience, increasing involvement in data- and technology-intensive functions, high levels of professional association membership, and participation in continuing education activities. Notably there are emerging role titles and job functions which point to a greater digital health focus in the changing work realm.Conclusion – The health librarian workforce has adapted its skills, in line with the increased digital emphasis in health information work. However, as with other health information occupational groups, it is possible that health system planners and funders are not aware of librarians’ current functions and skills. This mature workforce may undergo significant attrition and consequent loss of expertise in the next decade. Continued advocacy and strategic planning around these factors with workforce, healthcare quality, and educational organizations will be required.